2019
DOI: 10.4049/immunohorizons.1900065
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils Are More Effective than Monocytes at Phagosomal Containment and Killing ofListeria monocytogenes

Abstract: Neutrophils and inflammatory monocytes are innate immune cells essential for protection during Listeria monocytogenes infection. Although certain functions have been generally assigned to each of the cells, similarities and differences in functions necessary for bacterial clearance have not previously been investigated. In the current study, phagocytosis, phagosomal containment, bacterial killing, and cytokine production by neutrophils and monocytes during L. monocytogenes infection were studied. Data obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
(87 reference statements)
2
4
0
Order By: Relevance
“…However, recruited ADAP-deficient neutrophils appear to be inefficient in controlling pathogen growth, suggesting that they were not appropriately activated within the ADAP-deficient immune system. Of note, during Lm infection, monocytes are more efficient than neutrophils in the production of TNF-a and IL-1a (19), which is well in line with our data (Figure 3 and Supplementary Figure 3, left and middle panels). Moreover, production of TNF-a might enhance the ability of neutrophils to take up and kill Lm (19).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, recruited ADAP-deficient neutrophils appear to be inefficient in controlling pathogen growth, suggesting that they were not appropriately activated within the ADAP-deficient immune system. Of note, during Lm infection, monocytes are more efficient than neutrophils in the production of TNF-a and IL-1a (19), which is well in line with our data (Figure 3 and Supplementary Figure 3, left and middle panels). Moreover, production of TNF-a might enhance the ability of neutrophils to take up and kill Lm (19).…”
Section: Discussionsupporting
confidence: 91%
“…Of note, during Lm infection, monocytes are more efficient than neutrophils in the production of TNF-a and IL-1a (19), which is well in line with our data (Figure 3 and Supplementary Figure 3, left and middle panels). Moreover, production of TNF-a might enhance the ability of neutrophils to take up and kill Lm (19). Our data, however, did not reveal any correlation between TNF-a production and antibacterial function of neutrophils.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this context, it is important to also highlight pregnancy-induced changes in the frequency and tissue distribution of innate immune cells, including neutrophil and macrophage cells (28,75,76), both of which participate in protective immunity against E. coli and L. monocytogenes infections (38,(77)(78)(79)(80)(81). The cellular shifts that lead to infection susceptibility during pregnancy are likely linked with changes in systemic and local levels of innate inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, these results demonstrated that PMNs are the primary reservoir for Lm in the TME. This result was unanticipated, as we expected PMNs would rapidly kill phagocytosed Lm, preventing their escape into the cytosol and the expression of RFP [49][50][51] .…”
Section: Lm Infects Pmn-mdscs In Tumorsmentioning
confidence: 98%